Violence in the Religious Language of Christianity: Historical Analysis of Christian Religious Language Containing Violence as a Source of Critical Theology - Sariri, Meilina Simon (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
Historical fact indicates that the religious language of Christianity is rife with violence. The spiritual language is echoed in such bloody tragedies as war, murder, and punishment. This study aimed to encourage Christianity to understand violent religious language by viewing it in a reflective frame. The study uses qualitative methods to analyze history, so the literature that records the incidents of Christianity's involvement in violence is used. Analysis of the various literature produced two essential things as critical reflections on Christian theology. Based on historical facts of Christianity's involvement in violence, Christianity was at one time in a phase creating its doctrine (violence is not God's will), and Christianity played God (God did not engage in violence). That discovery is supposed to be part of a critical vehement from a violent point of view.